Liminality and the possibilities for sex and romance at an international bike meeting: a structural modeling approach - Milene Lança; João Filipe Marques; Patrícia Pinto (Tourism & Management Studies)
Sex and romance are part of the everyday life and the tourism experiences. Tourism is a liminal space-time which enables liminoid experiences such as a greater willingness for romance and sex, which can be the main motivators for travelling or an incidental activity, although possibly at a higher intensity. This research falls over an event where the festive environment combined to the liminoid states may contribute to enhance the availability for romance and sex. This correlation was tested using structural equation modeling applied to data collected in a sample of 449 individuals at Faro International Bike Meeting. The results suggest that bikers are motivated by the expectations of having sex and getting involved in a romance. The meeting environment influences the liminoid experiences which, in turn, activate sexual and romantic pleasures. Bikers are satisfied and intend to return, proving that a new market segment is rising up in the Algarve.